2012
DOI: 10.1016/j.ceca.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation/physiology of calcium channel sub-types in neurosecretory terminals

Abstract: The hypothalamic-neurohypophysial system (HNS) controls diuresis and parturition through the release of arginine-vasopressin (AVP) and oxytocin (OT). These neuropeptides are chiefly synthesized in hypothalamic magnocellular somata in the supraoptic and paraventricular nuclei and are released into the blood stream from terminals in the neurohypophysis. These HNS neurons develop specific electrical activity (bursts) in response to various physiological stimuli. The release of AVP and OT at the level of neurohypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 109 publications
1
41
0
Order By: Relevance
“…In our case, high K + induced a [Ca 2 + ] i increase that was blocked by 1 mM MVIIC in all tested cells, although the application of GVIA (500 and 800 nM), a selective N-type VOCC blocker, was not effective in blocking the K + -induced [Ca 2 + ] i. This could be explained by the presence of P/Q channels, which are sensitive to MVIIC but not to GVIA [30,36,43]. Indeed, the application of MVIIC at a 300 nM concentration, effective in blocking the P/Q-type of VOCC, reduced the Ca 2 + increase in all tested cells.…”
Section: Expression Of Vocc In P7 Hesc Npsmentioning
confidence: 60%
“…In our case, high K + induced a [Ca 2 + ] i increase that was blocked by 1 mM MVIIC in all tested cells, although the application of GVIA (500 and 800 nM), a selective N-type VOCC blocker, was not effective in blocking the K + -induced [Ca 2 + ] i. This could be explained by the presence of P/Q channels, which are sensitive to MVIIC but not to GVIA [30,36,43]. Indeed, the application of MVIIC at a 300 nM concentration, effective in blocking the P/Q-type of VOCC, reduced the Ca 2 + increase in all tested cells.…”
Section: Expression Of Vocc In P7 Hesc Npsmentioning
confidence: 60%
“…In isolated rat neurohypophysial nerve terminals, ATP stimulated the release of vasopressin (but only of minor amounts of oxytocin) via an increase in intracellular Ca 2+ concentrations, presumably through P2X2Rs [101][102][103]. In a later study, it was suggested that co-released ATP potentiates vasopressin release through the activation of P2X2Rs, P2X3Rs, P2X4Rs, and P2X7Rs whereas oxytocin release is mediated only through the P2X7R [100]. Using electrical stimulation of isolated and intact mouse posterior pituitaries, the concept was supported that the co-released endogenous ATP acts as a paracrineautocrine messenger, enhancing vasopressin secretion from neurohypophysial nerve terminals [104].…”
Section: Neuropeptides From the Hypothalamo-posterior Pituitary Unitmentioning
confidence: 99%
“…The endocrine hypothalamic-neurohypophysial system controls diuresis and parturition through the release of the neuropeptide hormones vasopressin and oxytocin [100]. Vasopressin and oxytocin are synthesized in the magnocellular neurons of the hypothalamus and released in the posterior pituitary (neurohypophysis).…”
Section: Neuropeptides From the Hypothalamo-posterior Pituitary Unitmentioning
confidence: 99%
“…As the initial [Ca 2+ ] i increase required extracellular Ca 2+ (Figs. 1(C and D)) and TRPM2 cation channels are known to be activated by cADPR, the initial [Ca 2+ ] i increase is likely to be due to influx of Ca 2+ through TRPM2 or equivalent cation channels: Such as other TRP canonical (Togashi et al, 2008), voltage dependent Ca 2+ channels (Tobin et al, 2011;Lemos et al, 2012), inositol-1,4,5 trisphosphate receptors (Maruyama et al, 1997), CRac channels (Zhou et al, 2007), and connexin36 (Bai et al, 2006), since 2-APB has multiple targets (Togashi et al, 2008). However, it has never reported that [Ca 2+ ] i increases through such Ca 2+ channels are temperature-sensitive (Tominaga and Caterina, 2004;Togashi et al, 2008 ] i was seen at >35 C ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…OT-induced OT release may be necessary in social recognition during nonreproductive daily life of both genders. A recent psychological study showed that CD38 is essential for OT release by the mean of Ca 2+ amplification following activation of voltage-dependent Ca 2+ channels (Lemos et al, 2012) and for maintenance of the basal intracranial level of OT (Kiss et al, 2011). Cyclic ADP-ribose (cADPR) is a catalytic product of -NAD + by internal ADP-ribosyl cyclase or membranebound CD38, a type II transmembrane glycoprotein (Lee et al, 2001;2006 and2011;Malavasi et al, 2008), and acts primarily as an intracellular second messenger that mobilizes Ca 2+ from intracellular Ca 2+ stores in various tissues (Galione et al, 1991;Lee et al, 1995;Lee, 2001 and2011;Higashida et al, 2007b and2012a).…”
Section: Introductionmentioning
confidence: 99%